Keterlibatan Ayah Dalam Aktivitas Bermain di Lingkungan Keluarga Terhadap Perkembangan Otak Anak Usia 3-5 Tahun - Fauziyah Rizkika; Krismayasari Krismayasari; Budi Iskandar (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Early childhood is considered a golden age period in which brain development is highly influenced by environmental stimulation, including play activities. Fathers’ involvement in play can support children’s cognitive, socio-emotional, language, and motor development. This study aimed to examine the relationship between fathers’ involvement in play activities and the development of brain function in children aged 3–5 years from a neuroscience perspective. The study employed a quantitative approach with a correlational design involving 30 fathers who had children aged 3–5 years in Tasikmalaya and surrounding areas. Data were analyzed using descriptive statistics, normality tests, linearity tests, and Pearson correlation analysis. The results showed a positive and significant relationship between fathers’ involvement in play activities and children’s brain function development (r = 0.412; p = 0.033 < 0.05), with a moderate correlation category. These findings indicate that fathers’ involvement in play contributes to children’s brain function development, although other factors such as mothers’ roles, nutrition, and educational environment also influence children’s development